2019
DOI: 10.1186/s13075-019-1815-0
|View full text |Cite
|
Sign up to set email alerts
|

In rheumatoid arthritis, changes in autoantibody levels reflect intensity of immunosuppression, not subsequent treatment response

Abstract: BackgroundRheumatoid arthritis (RA) is characterized by the presence of autoantibodies like rheumatoid factor (RF), anti-cyclic citrullinated peptide-2 (anti-CCP2), and anti-carbamylated protein (anti-CarP) antibodies. It is currently unclear whether changes in autoantibody levels are associated with disease activity/treatment outcomes and whether they are modified by treatment intensity. Therefore, we determined longitudinal changes in RA-autoantibody levels, the association between these changes and activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 15 publications
6
34
0
Order By: Relevance
“…It is unclear if this characteristic also applies to the anti-acetylated peptide antibodies (AAPA) 18 . These antibodies are remarkable in comparison with other new RA autoantibodies 18 23 . Perhaps, they are only comparable in reproducibility and apparent diagnostic characteristics to the anti-carbamylated protein antibodies (anti-CarP) 24 26 , although the two are less sensitive for RA than RF and anti-CCP antibodies.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is unclear if this characteristic also applies to the anti-acetylated peptide antibodies (AAPA) 18 . These antibodies are remarkable in comparison with other new RA autoantibodies 18 23 . Perhaps, they are only comparable in reproducibility and apparent diagnostic characteristics to the anti-carbamylated protein antibodies (anti-CarP) 24 26 , although the two are less sensitive for RA than RF and anti-CCP antibodies.…”
Section: Introductionmentioning
confidence: 82%
“…We do not know if this problem was punctual or has happened with additional reagent lots. In favour of the punctual problem is the use of the AAPA assays by other researchers without reporting any technical limitation [18][19][20][21][22][23] . It should be noted that caution and appropriate controls are always needed with this type of research assays that are not commercially available, nor approved for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, abatacept might directly reduce ACPA production but independently of its therapeutic effect. It was recently reported that changes in RAautoantibody levels were not associated with disease activity but reflected intensity of immunosuppression, although abatacept was not included in the analysis [15]. In addition, the presence of shared epitope rather than ACPA predicts clinical response to abatacept in RA [16], suggesting that ACPA might be an indicator of T cell-involvement in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, a broad autoantibody profile regarding different isotypes of RF, ACPA, and anti‐CarP is associated with early treatment response; but the importance of this broad profile diminishes over time . Intensity of treatment correlates with a decrease in autoantibody levels and reflects the level of immunosuppression, although this detectable decrease has only limited relevance for clinical activity and long‐term treatment response . These observations shed light on the possible role of autoantibodies in (pre‐)RA patients, although their exact functions need to be elucidated in future studies.…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 99%